Submarine landslides caused by the 2024 Noto Peninsula earthquake - Takafumi Kasaya; Hiroki Minami; Kyoko Okino; Junji Kaneko; Seitaro Ono (Earth, Planets and Space)
Abstract The 2024 Noto Peninsula earthquake (MJMA 7.6) occurred, followed by a tsunami on January 1, 2024. The earthquake caused considerable damage by strong ground motion over a wide area centered on the Noto Peninsula. The tsunami also damaged coastal areas. Japan Agency for Marine–Earth Science and Technology (JAMSTEC), Earthquake Research Institute (ERI) and Atmosphere and Ocean Research Institute (AORI) of the University of Tokyo conducted emergency survey cruises with various observations such as ocean bottom seismometers (OBSs) deployment and recovery operations to identify aftershock activity promptly and acquisition of multibeam bathymetry data from the northeast area of the Noto Peninsula and Toyama Bay. Our survey mainly covered the northeast part of the aftershock area and the downstream part of the Toyama Deep–Sea Channel (TDSC) in the Toyama Bay and the southern Toyama Trough. Survey lines in the northern survey area generally trend NNE–SSW, roughly parallel to the channel; some lines in the NNW–SSE direction cross the active faults. We compiled a bathymetric map (with 25 m grid spacing), using all available multibeam echo sounder (MBES) data. We identified some important bathymetric features, such as gentle wavy topography developed over the levee and horseshoe-shaped landforms. In addition, we conducted a dense survey to detect depth differences before and after the earthquake in the area along TDSC in the middle of our survey area. Results revealed four small-scale landslide areas in the dense survey area. Obtaining detailed topographic data using modern multibeam sonar is extremely important to assess the risk of tsunami damage for various marine infrastructures as well as the potential occurrence of submarine landslides and slope failures. Graphical Abstract